CASE BASED REASONING MENGGUNAKAN ALGORITMA BAYESIAN UNTUK PENENTUAN PEMBERIAN BERAS MISKIN - Erni Seniwati (Lembaga Penelitian dan Pengabdian (LPPM) STMIK Pelita Nusantara Medan, 2018)
Poor rice (Raskin) badly needed by families who are poor or less capable. Rice is a staple food for most humans. Granting Raskin still found still less on target due to the measurement data of each poor family or less capable in the selection with no maximum. In order for data selection can be done properly so that the granting of Raskin can be right on target so this research will use the concept of CBR. Case Based Reasoning (CBR) or also called Case-based Reasoning with (CPB) is a concept that can provide the output based on the happenings in the present compared with the incidence in the past in the form of a case. Bayes algorithm can be used on the concept of CBR on the process of retrieval and similarity. The process of retrieval and similarity using Bayes algorithm based on data the parameters of assessment (PP) and the data class eligibility. This research uses data parameters 9 assessment (PP) with code PP1 to PP9 and use 2 class class i.e. feasibility